Exploring the Accessibility of Community-Based Telerehabilitation for Children with Disabilities from Low-Income Households - Karen S. Sagun; Ryanne Nicole H. Alava; Kristine Therese S. Cablay; Katelyn A. Dagdag; Francis Rowelle P. Lagman; Kvaern Edgar S. Nocos; Jamela Y. Quidilla; Nina Mari M. Tan (International Journal of Telerehabilitation)
Community-Based Rehabilitation (CBR) is a rights-based approach that aims to provide equitable health services and participation opportunities for people with disabilities. Telerehabilitation has emerged as a potential methodology for delivering health care within the CBR framework. However, the accessibility of telerehabilitation presents unique challenges for children with disabilities (CWD) in communities with low socioeconomic status. This phenomenological qualitative study explores the barriers and facilitators that influence the participation of families of CWD in telerehabilitation as a method of CBR in urban poor communities. Nine focus group discussions (FGDs) were conducted involving 75 primary caregivers of CWD. Inductive thematic analysis using NVivo software was employed to analyze the collected data, revealing four themes that impact participation in Telerehabilitation: Economic and Social Resources, Self-Competency Affecting Transition, Flexible Service Delivery Mechanism, and Safety and Security as a Threat to Participation. The findings emphasize the intricate interplay of factors influencing the accessibility of telerehabilitation services for CWD from low-income households. Actionable strategies to address these challenges include providing affordable technology and internet access, offering training and support to families, developing culturally sensitive resources, establishing safety protocols, and advocating for inclusive policies and funding mechanisms. Collaboration among healthcare professionals, policymakers, and families is essential in building a resilient and equitable healthcare system that prioritizes the needs of CWD living in poverty. The insights gained from this study can inform the development of targeted interventions and support systems to ensure that no child is left behind in accessing quality care despite the digital and socioeconomic divides.